Representation of the concept “mind” in the karachay-balkar language - Akhmatova Mariyam A.; Ketenchiev Mussa B. (Актуальные проблемы филологии и педагогической лингвистики, 2018)
The article is devoted to the complex semantic characteristic of the concept “mind” in the Karachai-Balkar language, which is subjected to the multivariate analysis in the modern humanitarian science. In particular, its interpretation takes place in connection with the theory of action, as well as the identification of its diachronic and synchronic components based on texts of different genres. This phenomenon is a new object of study in the writings of the Karachai-Balkar philologists, who view it as a whole sporadically. The work identifies and describes the corpus of basic substantive lexemes relevant for the sphere of intelligence. Some of them are borrowings and some are the Karachai-Balkar proper words. It is noted that in this respect, adjectives and phraseological units that are oriented toward the representation of the intellectual abilities of the representatives of the Karachai-Balkarian ethnos are important. The concept “mind” in the most accumulated form finds its realization in the paremic statements of Karachais and Balkarians. Due to their specificity, they reflect the ethical, moral and intellectual components of the Karachai-Balkar language picture and are generally anthropomorphic in character and ethnoculturally labeled. Due to the anthropocentricity, proverbs and sayings contribute to the actualization of many anthropomorphic signs of a rational and perceptual plan. At the same time there is a mutual determination of concepts of the inner world and the reality surrounding him, which imposes an imprint on the worldview of a society. Being pragmatically loaded, they are generally didactic in nature and carry out a regulatory function with respect to the behavioral and other orientations of the native speaker, which predetermines their significant functional and semantic potential in the linguistic explication of such an important segment of the national language picture of the world as the intellectual sphere.